PERAN SKEPTISISME PROFESIONAL, TEKNOLOGI INFORMASI DAN ETIKA AUDITOR DALAM MENINGKATKAN KINERJA AUDITOR - Asrini Asrini; Ingka Ingka; Usman Rahman (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of professional skepticism, information technology, and auditor ethics on auditor performance at the Inspectorate of Sidenreng Rappang Regency. Auditor performance is an essential element in supporting accountability and transparency in regional financial management, especially in the public sector, which is vulnerable to irregularities and fraud. Auditors are required to work professionally, objectively, and ethically to ensure that financial statements are presented reliably and in accordance with applicable principles. This research uses a quantitative approach by distributing questionnaires to 36 auditors as respondents. The data analysis technique used is multiple linear regression. The results show that, partially, professional skepticism has a positive and significant effect on auditor performance, information technology has a positive and significant effect on auditor performance, and auditor ethics also has a positive and significant effect on auditor performance. Simultaneously, these three variables also have a positive and significant influence on auditor performance. These findings strengthen attribution theory and the Technology to Performance Chain (TPC) model, and emphasize the importance of professional skepticism, technological competence, and auditor ethics in improving auditor performance.